Membrane lipid signaling in aging and age-related disease - Mattson, Mark Paul (Advances in cell aging and gerontology, 2003)
The lipids of cellular membranes not only serve roles in controlling the structure and fluidity of the membrane, but are increasingly recognized for their roles as signalling molecules and modifiers of membrane protein function. Recent studies described in this volume reveal striking changes in membrane lipids during aging and in age-related diseases such as cancer, cardiovascular disease and neurodegenerative disorders. Lipids including inositol phospholipids, cholesterol, sphingolipids and ceramides play important roles in signalling cellular responses to stress and specific stimuli such as growth factors, cytokines and neurotransmitters. One or more of these lipid mediators has been linked to the pathogenesis of age-related diseases. This book provides a comprehensive review of specific membrane lipid mediators and their roles in aging and age-related disease.